A descriptive study on rubber dam used in endodontic practice in dental clinics in Ermita Manila - Gumawid, Alphon Andrew S.; Rabino, Dindo A.; Galban, Angelita B. (Adviser).
Rubber dam is a dental material that can maintain the appropriate dryness of the working field, provide gingival and tongue retraction, prevent accidental swallowing of any small instrument or debris, and allow avoidance of too much aerosols. It is an essential tool for achieving proper isolation which is a huge factor for a successful endodontic procedure. Even though dentists are aware of these advantages, rubber dam is still ignored and abandoned by some dental practitioners. This descriptive study focused on determining the number of rubber dam users and the reasons, factors and feedbacks of practicing dentists on the use of rubber dam in endodontic procedures in their private practice. The study was conducted through the use of a survey questionnaire which was distributed among 34 practicing dentists who performs endodontic treatment in Ermita Manila. Out of the 30 respondents, 29 have used rubber dam in their private practice. Most of the frequent users came from the younger age dentists. Several factors that affect the dentist preference in using rubber dam in practice were found to be age, gender, year graduated, type of practice, tooth to be isolated and the training and education on rubber dam application.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental materials; Endodontics; Rubber dam